Asymmetric Brønsted acid-catalyzed aza-Diels–Alder reaction of cyclic C-acylimines with cyclopentadiene - Rueping, Magnus; Raja, Sadiya (Beilstein Journal of Organic Chemistry, 2012)
A new chiral Brønsted acid-catalyzed aza-Diels–Alder reaction of cyclic C-acylimines with cyclopentadiene has been developed. The reaction provides optically active aza-tetracycles in good yields with high diastereo- and enantioselectivities under mild reaction conditions.
Keywords: BINOL phosphate; [4 + 2] cycloaddition; Diels–Alder reaction; organocatalysis